Bibliometric Analysis: Current Trends in the Relationship between Learning Motivation and Student Performance through the Influence of Learning Media, with a Focus on Augmented Reality in the Educational Context - Irfan Andi Gaffur; Nur Islami; Almasdi Syahra; Suarman Suarman (Instructional Development Journal, 2024)
This bibliometric research analyzes 38 publications related to education over the past four years, focusing on the relationship between learning motivation and student performance. The analysis aims to determine the influence of learning media, especially Augmented Reality (AR), on student motivation and performance. A qualitative descriptive method is employed to detail data from international journal articles indexed in Scopus (Q1-Q2). The study also applies a systematic analysis using the PRISMA method to identify relevant articles. The analysis results indicate that keywords such as "Motivation," "Digital Medium," "Development," and "Outcome" dominate the research focus. Additionally, Augmented Reality is identified as a major trend in learning media. These findings provide in-depth insights into current research trends in educational management, with an emphasis on the significant role of learning media, especially Augmented Reality, in enhancing learning motivation and student performance.